Membangun Kesadaran Mata Uang Nasional : Sosialisasi Rupiah Pada Anak-Anak di Desa Manyang Kecamatan Meurah Mulia - Maulina, Isra; Sufrizal, Sufrizal; Iskandar; Rita Mulyani; Putri Sakinah Muti (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
The Rupiah is a strong symbol of national identity. Fostering a sense of pride and love for this currency helps strengthen national unity and identity. Manyang Village itself is one of the villages that is located quite far from the city of Lhokseumawe, in this village there are still many children who don't understand and still don't receive enough education about rupiah money, especially CBP (love, pride, understanding) of rupiah so many children are breastfed. Many people are less aware of the amount of currency and how to protect and care for that currency. Therefore, it is necessary to instill a sense of love, pride and understanding of the rupiah currency in these children. The methods used in this work program are socialization and education. The stages carried out in this work program include: Planning, implementation and evaluation. This service aims to foster a sense of love, pride and understanding of the rupiah. The methods used in service are planning, implementation and evaluation. The results of this service show that this socialization can increase feelings of love and pride, financial education and know that money is a symbol of state economic sovereignty for children in the Desa Manyang area regarding the Rupiah currency.